2013
DOI: 10.1093/toxsci/kft017
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Alterations Following Developmental Atrazine Exposure in Zebrafish Are Associated with Disruption of Neuroendocrine and Reproductive System Function, Cell Cycle, and Carcinogenesis

Abstract: Atrazine, a herbicide commonly applied to agricultural areas and a common contaminant of potable water supplies, is implicated as an endocrine-disrupting chemical (EDC) and potential carcinogen. Studies show that EDCs can cause irreversible changes in tissue formation, decreased reproductive potential, obesity, and cancer. The U.S. Environmental Protection Agency considers an atrazine concentration of ≤ 3 ppb in drinking water safe for consumption. The specific adverse human health effects associated with a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
98
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 39 publications
(63 reference statements)
4
98
1
Order By: Relevance
“…A previous study in the Freeman laboratory provided insight into atrazine exposure during embryogenesis of the zebrafish (Weber et al, 2013). The study encompassed the developmental time points of 1 to 72 hours postfertilization (hpf; the end of embryogenesis) and exposure of atrazine at various concentrations (0, 0.3, 3, or 30 ppb) to understand the effects of atrazine during development.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study in the Freeman laboratory provided insight into atrazine exposure during embryogenesis of the zebrafish (Weber et al, 2013). The study encompassed the developmental time points of 1 to 72 hours postfertilization (hpf; the end of embryogenesis) and exposure of atrazine at various concentrations (0, 0.3, 3, or 30 ppb) to understand the effects of atrazine during development.…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptomic study revealed alterations in expression in a couple hundred genes, some of which have known roles in carcinogenesis. Of these genes, expression studies through (quantitative polymerase chain reaction) qPCR and western blot were conducted and cyp17a1, glo1, sik2, and tpd52l1 displayed significant upregulation in gene and protein expression at 72 hpf (Weber et al, 2013). The role of these genes goes beyond carcinogenesis; they have shown connections to cell cycle regulation, cell signaling, and reproduction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations